Comunicação com mães de neonatos sob fototerapia : pressupostos humanísticos - Campos, Antônia do Carmo Soares (2005)
The process of communication of the heath team with the mother whose child is under phototherapy is fundamental so that she can calm down and become acquainted with the treatment. The thesis defended in this research is that the communication permeated by the Nursing humanistic care will contribute to the mother of the newborn under phototherapy come to know, understand the treatment and this way be well and be - better. We aimed to analyze the communication with mothers of newborns under phototherapy through the Phenomenological Nursing Process of the Paterson and Zderad’s Humanistic Theory. Qualitative, exploratory and descriptive study, instrumentalized through the mentioned process, in five stages: the preparation of the nurse to come to know; the nurse knows intuitively the other; the nurse knows scientifically the other; the nurse synthesizes in a complementary way the known realities; the internal succession of the nurse starting from many to an only paradoxical. It had as environment a public maternity hospital in Fortaleza-CE. The subjects were 25 mothers taken into the referred institution, whose newborn (NB) children were under phototherapic treatment in the Neonatal Care Unit (NCU) of high, medium risk and/or Shared Accommodation (SA), from January to March/2005. We used as technique the participant observation and the individual interview, in two phases, with the following orienting question “What does it mean for you, mother, to witness your child under phototherapy?” In the data analysis of the participant observation we could visualize the interactions mother/newborn/nurse. From the speeches extracted from both phases of the interview the following themes were identified communication, knowledge, care, perception and feelings. From the theme communication, we extracted in the first phase the sub-themes damaged communication with the health team; lack of communication of the health team and communication mother–newborn; and in the second phase, reactions of the mother after effective communication of the nurse. From the theme knowledge, we extracted in the first phase the sub-themes lack of knowledge about phototherapy and search for knowledge about phototherapy and in the second phase, acquired knowledge about phototherapy and comprehension of the phototherapic treatment: a new vision of the mother. From the care theme, we extracted in the first phase the sub-theme the newborn under phototherapy – mothers searching Nursing Care and in the second phase, care-presence: participation of mothers in the care to newborn under phototherapy and didactic resource in the communication process: subsidy to Nursing care with mothers of newborns under phototherapy. From the theme perception, we extracted in the first phase the sub-themes health of the newborn under phototherapy: the vision of the mother; separation of the binomial mother-son; the mother of the newborn under phototherapy and the hospital environment; and in the second phase, health of the newborn under phototherapy: what has changed? From the theme feelings, we extracted in the first phase the sub-theme impotence and sadness and in the second phase, mothers before the newborn under phototherapy: well-being and be better. As we concluded, the effective communication of the nurse contributed for the mothers to calm down and be better while they experience their child under phototherapy.